Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat Desa Bengkuang Kecamatan Suak Tapeh Kabupaten Banyuasin - Isma Nirmala (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Assessment of the quality of public service performance is also an assessment of the quality of government performance because the government is responsible for public services. The better the quality of public services organized by the government, the higher the level of community satisfaction with the government's work. Good public services are not only the obligation of the government at the central, provincial, or city and district levels, but are also needed at the village government level. This study aims to analyze the effect of public service quality on community satisfaction in Bengkuang Village, Suak Tapeh District, Banyuasin. The research approach used is a quantitative approach. The data used is primary data with data collection method using a questionnaire instrument. The sample taken is as many as 85 respondents. The analysis technique used is Simple Linear Regression Analysis. The results showed that the quality of public services at the Bengkuang Village Office had a positive and significant effect on community satisfaction in Bengkuang Village..